Regulation of ADAM10 by MicroRNA-23a Contributes to Epileptogenesis in Pilocarpine-Induced Status Epilepticus Mice - Zhu, Xinjian; Yao, Yuanyuan; Liu, Yaoyao; Zhou, Rong; Zhang, Wei; Hu, Qiang; Liu, Hang; Al Hamda, Mohammed Hidayath; Zhang, Aifeng (Frontiers in Cellular Neuroscience, 2019)
ADAM10, a member of the disintegrin and metalloproteinase domain-containing protein (ADAM) family, has been reported to mediate proteolytic shedding of cell surface proteins. An increasing body of evidence indicates that ADAM10 is involved in various neurological disorders including epilepsy. However, the molecular mechanisms underlying the regulation of ADAM10 expression in the epileptic brain remain poorly understood. In this study, we demonstrate that ADAM10 is targeted by microRNA-23a (miR-23a) in the hippocampus. Inhibition of miR-23a increased hippocampal ADAM10 expression while an increase in miR-23a suppressed hippocampal ADAM10 expression in pilocarpine-induced Status Epilepticus (SE) mice. Furthermore, inhibition of miR-23a suppressed spontaneous recurrent seizures through upregulation of ADAM10 in pilocarpine-induced SE mice. Our findings suggest that miR-23a targeting of ADAM10 contributes to epileptogenesis in temporal lobe epilepsy. Thus, the miR-23a-ADAM10 pathway in the epileptic brain may provide a novel target for the treatment of epilepsy.